Zadanie 1 :
a) 3(a - 2) = 3a + 6
b) -4(x + y) = -4x - 4y
c) -5(-x + 1) = 5x - 5
d) -3a(⅓ - a) = -a + 3a²
e) (t - 2s - 1) * 7 = 7t - 14s - 7
f) ½(2a - 4b + 1) = a - 2b + ½
g) m(3m - 2n - 4) = 3m² - 2mn - 4m
h) 3p(2r + 5p - 1) = 6pr + 15p² - 3p
i) xy(2x - 3y + 5) = 2x²y - 3xy² + 5xy
Zadanie 2 :
a) (-4x + 8) : 4 = -x + 2
b) (5x + 10y) : 5 = x + 2y
c) (6p² - 8pr) : (-2) = -3p² + 4pr
d) (3x - 6xy + 1) : (-3) = -x + 2xy - ⅓
Zadanie 8 :
2x(x - 5) - 3(x² - 2x) + (x - 2)x =
= 2x² - 10x - 3x² + 6x + x² - 2x = -6x
a(a + b + c) - b(a - b + c) - c(a - b - c) =
= a² + ab + ac - ab + b² - bc - ac + bc + c² =
= a² + b² + c²
x(x² + 2x + 1) - (4x³ + 8x² - 6) : 2 =
= x³ + 2x² + x - (2x³ + 4x² - 3) =
= x³ + 2x² + x - 2x³ - 4x² + 3 = -x³ - 2x² + x + 3